Youth culture and urban pride; The sociolinguistics of East Javanese slang - Hoogervorst, Tom G. (Wacana, Journal of the Humanities of Indonesia, 2014)
This study offers an overview of the characteristics and social functions of youth slang in the Indonesian province of East Java. It examines Boso Walikan and various types of Surabayan slang. Boso Walikan emerged in Malang as a secret language that was deliberately made unintelligible to outsiders. Over the decades, large parts of Malang's urban population developed proficiency in the language and appropriated it as an identity marker. The situation in nearby Surabaya is different. While lacking a uniform local slang comparable to that of Malang, several communities make an effort to differentiate themselves through specific linguistic habits, which are briefly introduced. These case studies tell us not only how young people shape their speech, they illustrate how the East Javanese dialect deals with linguistic variety, lexical borrowing and innovation.